2003
DOI: 10.1515/jpm.2003.076
|View full text |Cite
|
Sign up to set email alerts
|

Fetal hand movements and facial expression in normal pregnancy studied by four-dimensional sonography

Abstract: 4D-US is superior over real-time two-dimensional ultrasound (2D-US) for qualitative, but inferior for quantitative analysis of hand movements. Thus 4D-US makes it possible to determine exactly the direction of the fetal hand, but the exact number of each type of hand movements can still not be determined. 4D-US is superior over two- and three-dimensional sonography in the evaluation of complex facial activity and expression. Among facial activities observed by 4D-US, simultaneous eyelid and mouthing movements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
130
7
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(151 citation statements)
references
References 9 publications
7
130
7
6
Order By: Relevance
“…1,6,30 However, we have found that the quality of movements is affected by spatial constraints, as can be observed in near-term fetuses that perform movements with a reduced amplitude. Furthermore, the intrauterine environment may be affecting movement quantity.…”
Section: Figmentioning
confidence: 49%
See 1 more Smart Citation
“…1,6,30 However, we have found that the quality of movements is affected by spatial constraints, as can be observed in near-term fetuses that perform movements with a reduced amplitude. Furthermore, the intrauterine environment may be affecting movement quantity.…”
Section: Figmentioning
confidence: 49%
“…30,34 With MR imaging providing a fuller appreciation of the intrauterine environment, we observed that the fetal posture appears to facilitate the adduction of the arms toward the midline and the flexion of the hands toward the face across the age range studied (Fig 3A,-B). It is difficult to quantify the effect that the shape of the uterus has on determining this posture, though coronal sections through the fetal body show that from GA 20 weeks, there is negligible amniotic fluid on its lateral aspects (Fig 3A), with collections located mostly anterior and posterior to the fetus (Fig 3B).…”
Section: Figmentioning
confidence: 90%
“…[33][34][35]37,[39][40][41] All studies focused on the assessment of fetal facial expressions and movements, and fetal hand to face movements (Figs 6A to 8), because the viewing area was limited to that of the transabdominal probe. Kurjak et al 37 were the first to use 4D sonography to study 10 healthy fetuses for 15 minutes at 30 to 33 weeks. Among facial activities observed by 4D sonography, simultaneous eyelid and mouthing movements dominated between 30 and 33 weeks of gestation.…”
Section: Late Second and Third Trimestersmentioning
confidence: 99%
“…O estudo da atividade fetal por meio da ultrassonografia considerando as quatro dimensões, quais sejam, a altura, a largura, a profundidade e contando o tempo como a quarta dimensão, forneceu uma nova ferramenta para a observação da diferenciação do movimento, proporcionou a visualização simultânea de todas as quatro extremidades e permitiu o reconhecimento de movimentos isolado e delicados do braço e sua direção. Esse conhecimento trouxe avanços na relativa inexplorada área do comportamento fetal bem como a mensuração do desenvolvimento neurológi-co 12 .…”
Section: Movimentos Dos Membros Superiores No Feto Humanounclassified
“…A fre-revisão quência dos movimentos isolados do braço aumentou gradualmente da 8ª à 19ª semanas. Todos os movimentos eram observados na 13ª semana de gestação, com moderada flutuação na frequência 12 . Movimentos das mãos de fetos de gestações de baixo risco foram pesquisados durante a 14ª, 20ª, 26ª, 32ª e 37ª semanas de gestação e no 1º dia de vida pós-natal.…”
Section: Movimentos Dos Membros Superiores No Feto Humanounclassified